Architecture of Counterrevolution The French Army in Northern Algeria - Henni, Samia (Architectural Knowledge, 2017)
After over 120 years of French colonial rule in Algeria, the growing aspirations for independence culminated in the Algerian Revolution of 1954, which lasted until 1962. In order to combat the uprisings, the French civilian and military authorities reorganized the entire territory of the country, swiftly erected new infrastructures and pursued building policies that were ultimately intended to stabilize French dominance in Algeria. The study describes the architectural responses undertaken in the midst of this protracted and bloody armed conflict. It analyses their origins, evolutions and objectives, identifies the actors involved and reveals the underlying design methods.